Hinterland evolution and port growth decomposition: The case of Shanghai. (April 2022) - Wan, Shulin; Luan, Weixin
Abstract: The 2008 global financial crisis led directly to the reduction of seaborne trade volume. Competition for hinterlands by ports has become increasingly fierce, and the hinterlands and driving factors of port growth are constantly evolving. Identifying port hinterlands and the source of port container volume growth is essential to the sustainable development of ports. Taking Shanghai Port as an example, this paper adopts the membership degree-Huff model to analyze the evolution of the foreign trade container hinterlands of the port from 2009 to 2017. The results show that, because the hinterland is constantly being permeated by competing ports, Shanghai Port has gradually begun to expand its hinterland coverage to cities outside the traditional hinterlands, mainly in the northern areas. This paper introduced the Logarithmic Mean Divisia Index decomposition method to port growth research for the first time. The decomposition model of driving factors of port growth was constructed from the perspective of the hinterland. We found that, while the growth effect and spatial structure effect promote the increase of foreign trade containers in the port, the competitiveness effect leads to the decline of these. In future, government departments should promote cooperation among ports in the Yangtze River Delta to facilitate strategic coordination of the free trade (pilot) zone, resource sharing, and policy integration. In addition, Shanghai Port should devote itself to the development of a high value-added shipping services industry cluster to consolidate and enhance its international shipping status and functions. Highlights: Shanghai Port was in fierce competition with neighboring ports. The port growth decomposition was constructed from the hinterland perspective. The growth effect and spatial structure effect lead to the increase of foreign trade containers in Shanghai Port. The competitiveness effect leads to the decline of foreign trade containers in Shanghai Port.